From an Empire to a Nation State: Importing the Concept of Nation into Ottoman/Turkish Thinking - Daldeniz, Elif (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2014)
During importation processes of concepts, the target context and the agents involved in these processes are central and shape the imported ideas. Hereby, translation, both in its narrow and broader senses, plays an important role. The aim of this article is to present preliminary research results on the importation process of the concept of nation into the Ottoman/Turkish culture as the target culture. The article provides research results gained from the analysis of dictionaries as well as of texts written by important figures of Turkish nationalism during the last decades of the Ottoman Empire. The research covers first-hand analysis of key texts by Yusuf Akçura and Ziya Gökalp whereby the use of the concept of ‘nation’ by other key figures are discussed on the basis of secondary sources. The analysis also includes translations. This study, which is linked to a study on the concept of ‘culture,’ was based on an interdisciplinary approach relying on the perspectives and notions of translation studies and on methodology developed in conceptual history. The theoretical framework and methodology adopted in this study are exposed in the first part, whilst the second part presents and discusses the research results.